Long‐term effects of face masks on skin characteristics during the COVID‐19 pandemic. Issue 1 (19th October 2021) - Park, Sae‐Ra; Han, Jiyeon; Yeon, Yeong Min; Kang, Na Young; Kim, Eunjoo; SUH, Byung‐Fhy
Abstract: Background: Nowadays, face masks are a crucial part of our daily life. Previous studies on their impact on the skin usually focused on the adverse effects of face masks. Few studies have assessed their influence on skin characteristics. In a previous study, we identified the short‐term effects of wearing face masks. Herein, we describe the long‐term skin effects of face masks, for a period of 6 months. Materials and methods: Healthy volunteers (19 men and women), who wore face masks, participated in the study from June 2020 to December 2020. In all participants, skin characteristics such as trans‐epidermal water loss (TEWL), skin hydration, skin elasticity, skin pore area, skin keratin amount, skin temperature, skin redness, skin temperature, skin redness, and skin color were measured three times. Results: TEWL, skin hydration, skin elasticity, skin pore area, skin keratin amount, and skin color changed significantly after 6 months. TEWL, skin hydration, skin pore area, skin keratin amount, and skin color were significantly different between the mask‐wearing and non‐mask‐wearing areas. Conclusion: Long‐term daily use of face masks can alter skin characteristics. Special care should be focused on the mask‐wearing regions.